2015
DOI: 10.1186/s13002-015-0045-z
|View full text |Cite
|
Sign up to set email alerts
|

An ethnomedicinal study of the Seri people; a group of hunter-gatherers and fishers native to the Sonoran Desert

Abstract: BackgroundWorldwide, coastal communities’ ethnomedicinal knowledge has been sporadically recorded and poorly understood. Based on the ethnomedicinal knowledge of the Seri people; a hunting-gathering and fishing society of Northwestern Mexico, this study assesses a) the biological richness of Seri ethnomedicinal knowledge, b) the fidelity level of Seri remedies, and c) the association between gender, age, years of formal schooling and Seri ethnomedicinal knowledge.MethodsTo assess the degree of ethnomedicinal k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 77 publications
0
5
0
1
Order By: Relevance
“…Unlike the reported for some indigenous communities (Eyssartier et al 2011, Cruz et al 2013, Sujarwo et al 2014, Narchi et al 2015, knowledge erosion was no observed among the younger and the older male ranchers, at least in the number of species they cited. This result agrees with the reported for a non-indigenous community in Rayones, Nuevo León, Mexico; however, unlike our finding, they found that women cited more species (edible and no edible) than men (Estrada-Castillon et al 2014).…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Unlike the reported for some indigenous communities (Eyssartier et al 2011, Cruz et al 2013, Sujarwo et al 2014, Narchi et al 2015, knowledge erosion was no observed among the younger and the older male ranchers, at least in the number of species they cited. This result agrees with the reported for a non-indigenous community in Rayones, Nuevo León, Mexico; however, unlike our finding, they found that women cited more species (edible and no edible) than men (Estrada-Castillon et al 2014).…”
Section: Discussionmentioning
confidence: 48%
“…Mexico also has a long tradition in ethnobotanical studies, which are the basis to select wild plants for use, conservation and domestication purposes. However, most of these studies have been focused in population of the south-central region (the states of Puebla, Oaxaca, Veracruz, Yucatán, Morelos, Guerrero, Tabasco, Mexico, and Hidalgo) and indigOaxaca, Veracruz, Yucatán, Morelos, Guerrero, Tabasco, Mexico, and Hidalgo) and indigenous (mainly Maya, Nahua, Mixtec, Otomí, and Totonac) people (Caballero et al 1998, Yetman & Van Devender 2002, Camou-Guerrero et al 2008, Vázquez-Alonso et al 2014, Narchi et al 2015, Camou-Guerrero et al 2016, whereas other people living immerse in nature with their own accumulated knowledge have been relegated, as it occurs with the ranchers. Some examples of ethnobotany works in Mexican non-indigenous rural communities are the studies about the native tree species used by ranchers of the central Veracruz (Suárez et al 2012), the medicinal plants used by ranchers of Tabasco (Gómez-Álvarez 2012), and the ethnobotany of farmers in Rayones, Nuevo León (Estrada-Castillon et al 2014).…”
Section: Juan Fernando Pío-león Et Almentioning
confidence: 99%
“…In one of the first written health reports on the Seris, dating back to the mid-1950s, Alejandro Marroquin (1957) noted that, despite the healthy appearance of the people, there was a recurrence of gastrointestinal diseases among the population; such health care demands remained constant for nearly five decades (Narchi et al 2015).…”
Section: Discussion: What Happened To Seri Sweets?mentioning
confidence: 99%
“…Evidence suggests Seri residence in the region for at least a thousand years (Haynes et al 1966). Although there has been considerable loss of traditional information due to acculturation (Felger and Moser 1973), the Seris still extensively rely on marine and desert resources (Bertsch and Marlett 2011; Narchi et al 2015), including—though declining—the use of local sweets. Based on the historic dietary pattern and drawing a parallel with other small-scale societies (Pontzer et al 2018), it can be inferred that the local diet was rich in carbohydrates and simple sugars, in contrast to the current use of highly caloric, industrialized foods.…”
Section: Methodsmentioning
confidence: 99%
“…También hay, inter alia, los que se desenvuelven en la teoría de sistemas complejos (Hughes et al, 2005), etnobiología (Narchi et al, 2014), nutrición (Hernández-Santana y Narchi, 2018), etnoecología (Lloret et al, 2014), etnomedicina (Narchi et al, 2015) y etno-oceanografía (Moura, 2017a).…”
Section: Las Oceanografías Sociales: Evolución De Un Campo De Estudiounclassified